Can curriculum be an inspiration for physical education teacher - Umiastowska, Danuta (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The purpose of education is preparing a student for safe participation in whole life physical activity featuring recreational and sport elements, with understanding its meaning to one’s health. A teacher in cooperation with students is responsible for conveying the process of education. Student should not be only a participant, but also a partner. Effects depend on creativity of teachers. A creative teacher can be characterized by three key competences: diagnostic abilities, abilities of stimulation and supporting development of a talented student as well as helping with overcoming barriers and crystallisation of student’s abilities. In the presented study the following questions were supposed to be answered: What inspires a teacher to undertake creative activities? What is the role of curriculum in such a process?